Inflammation induces pro-NETotic neutrophils via TNFR2 signaling - Neuenfeldt, Friederike S.; Schumacher, Jan-Christoph; Grieshaber-Bouyer, Ricardo; Habicht, Jüri; Schröder-Braunstein, Jutta; Gauss, Annika; Merle, Uta; Niesler, Beate; Heineken, Niko; Dalpke, Alexander; Gaida, Matthias; Giese, Thomas; et al. (Cell reports, 2022)
Cytokines released during chronic inflammatory diseases induce pro-inflammatory properties in polymorphonuclear neutrophils (PMNs). Here, we describe the development of a subgroup of human PMNs expressing CCR5, termed CCR5+ PMNs. Auto- and paracrine tumor necrosis factor (TNF) signaling increases intracellular neutrophil elastase (ELANE) abundance and induces neutrophil extracellular traps formation (NETosis) in CCR5+ PMNs, and triggering of CCR5 amplifies NETosis. Membranous TNF (mTNF) outside-in signaling induces the formation of reactive oxygen species, known activators of NETosis. In vivo, we find an increased number of CCR5+ PMNs in the peripheral blood and inflamed lamina propria of patients with ulcerative colitis (UC). Notably, failure of anti-TNF therapy is associated with higher frequencies of CCR5+ PMNs. In conclusion, we identify a phenotype of pro-NETotic, CCR5+ PMNs present in inflamed tissue in vivo and inducible in vitro. These cells may reflect an important component of tissue damage during chronic inflammation and could be of diagnostic value.